CRC handbook of modern telecommunications (CRC Press, 2010)
This handbook surveys emerging telecommunication systems and the role they will play in the future. In addition to this second edition's new discussions of radio frequency identification (RFID) and wireless sensor networks, the book contains sections on techniques of voice communication systems, the structure of the Internet and how it will handle future services, network management and administration, and network organization and govnernance.